1993
DOI: 10.1080/09540129308258594
|View full text |Cite
|
Sign up to set email alerts
|

“I plan to have the HIV test”—predictors of testing intention in women attending a London antenatal clinic

Abstract: In order to identify which factors predict a parturient womans intention to take up voluntary HIV testing in the antenatal clinic, 318 women were surveyed by anonymous self-completion questionnaire. The strongest predictors of intention to be tested were the perceived benefit of the test to the woman herself, her partner, and the midwife, perceived risk of HIV infection, younger age and being single and having a poor knowledge of the sexual routes of HIV transmission. Health education strategies should therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…The difference between perceived willingness to participate in VCT and PMTCT underscores that a perceived benefit from participation is a crucial factor for acceptance of HIV testing (Fylkesnes et al, 1999;Meadows et al, 1993).…”
Section: Discussionmentioning
confidence: 96%
“…The difference between perceived willingness to participate in VCT and PMTCT underscores that a perceived benefit from participation is a crucial factor for acceptance of HIV testing (Fylkesnes et al, 1999;Meadows et al, 1993).…”
Section: Discussionmentioning
confidence: 96%
“…This is an important finding since it suggests that church affiliates in marriage or cohabiting relationships may not know their current HIV status. Past studies have found mixed results related to marital status as an HIV screening predictor (Heffelfinger et al, 2009; Inungu et al, 2005; Mack & Bland, 1999; Meadows, Catalan, & Gazzard, 1993). However, considering the changing demographics of new HIV cases, particularly with increased HIV risk for African American women through heterosexual contact, targeted HIV awareness efforts may be needed to increase HIV screening among church affiliates who are married, cohabiting, or entering new relationships, especially since studies suggest that African American men are twice as likely to have concurrent sexual partners.…”
Section: Discussionmentioning
confidence: 99%
“…Conforming to a social norm and feeling good about one's own health have also been suggested as reasons some individuals decide to test (Kalichman et al, 1997). The potential health benefits that may motivate increased testing include receiving early highly active antiretroviral therapy (Palella et al, 1998), and, for pregnant women, the prevention of transmission to their infants (Meadows et al, 1993).…”
Section: Lauby Bond Eroglu and Batsonmentioning
confidence: 99%